Gunshot in a yellow-headed caracara (Mivalgo chimachima): case report - Perles, L.; Kawamoto, F. Y. K.; Couto, C.; Werther, K.; Minto, B. W. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2018)
Anthropogenic injuries have been frequently described in raptorial, including habitat destruction, pollution, car collisions, structure impacts, and poaching by trap or gunshot. (PUNCH, 2001). In Brazil, hunting or trapping of any free-living animal, including birds of prey species is forbiden by the law number 5.197, from January 3th, 1967 (INSTITUTO CHICO MENDES DE CONSERVAÇÃO DA BIODIVERSIDADE, 2008) and by the art. 29 of the Environmental Crimes, Law 9.605/98 (BRASIL, 1998). In spite of this law, it is frequent in the wild animal clinic to receive birds with fractures and internal organ damage caused by firearm projectiles. There are several studies in other countries which demonstrate that hunting is an important factor causing mortality of these animals, especially raptors (DEEM; TERRELL; FORRESTER, 1998; PUNCH, 2001; WENDEL; SLEEMAN; KRATZ, 2002). This case report is the description of multiple fractures caused by gunshot in a Yellow-headed caracara (Mivalgo chimachima).